Sumienie. Aspekty psychologiczne i pedagogiczne - Hanisch, Helmut (Horyzonty Wychowania, 2017)
The author ponders over one of the main anthropologicalissues concerning the process of man’s upbringing, namely thepossibilities of educating human conscience. Three psychologicalconcepts: Sigmund Freud’s psychoanalysis, Carl Gustav Jung’sneopsychoanalysis and Philip Lersch’s personality psychologyformed the background to his pedagogical reflections. The presentationof each scholar’s views ends with a conclusion formulatedon the basis of the question about the possibility to inferthe foundations (also axiological) for a particular pedagogy froma given psychological conception.The closest to the author and also, in his opinion, the mostfruitful for the process of upbringing is Philip Lersch’s conceptemphasizing the role of the experience of sense in the formationof human conscience. In order to develop and deepen this directionof deliberations, the author refers to Eric Erickson’s concept,for which the key moment linking experiencing the worldand building this feeling of sense is prime confidence.In the last part of the study the author, searching for a broaderaxiological horizon conditioning the formation of conscience, refersto a transcendent perspective, possible to express also inreligious values. For the upbringing process, however, consciencehas the fundamental meaning, not so much the „transmoral-religious” as „moral-ethic conscience”, which „operates” onlywhen it is accompanied by a deep sense of obligation to particularvalues, and also joy and pleasure resulting from fulfillingthem.